Proteomic Responses to Ocean Acidification in the Brain of Juvenile Coral Reef Fish - Tsang, Hin Hung; Welch, Megan J.; Munday, Philip L.; Ravasi, Timothy; Schunter, Celia (Frontiers in Marine Science, 2020)
Elevated CO2 levels predicted to occur by the end of the century can affect the physiology and behaviour of marine fishes. For one important survival mechanism, the response to chemical alarm cues from conspecifics, substantial among-individual variation in the extent of behavioural impairment when exposed to elevated CO2 has been observed in previous studies. Whole brain transcriptomic data has further emphasized the importance of parental phenotypic variation in the response of juvenile fish to elevated CO2. In this study, we investigate the genome-wide proteomic responses of this variation in the brain of 5-week old spiny damselfish, Acanthochromis polyacanthus. We compared the accumulation of proteins in the brains of juvenile A. polyacanthus from two different parental behavioural phenotypes (sensitive and tolerant) that had been experimentally exposed to short-term, long-term and inter-generational elevated CO2. Our results show differential accumulation of key proteins related to stress response and epigenetic markers with elevated CO2 exposure. Proteins related to neurological development and glucose metabolism were also differentially accumulated particularly in the long-term developmental treatment, which might be critical for juvenile development. By contrast, exposure to elevated CO2 in the parental generation resulted in only three differentially accumulated proteins in the offspring, revealing potential for inter-generational acclimation. Lastly, we found a distinct proteomic pattern in juveniles due to the behavioural sensitivity of parents to elevated CO2, even though the behaviour of the juvenile fish was impaired regardless of parental phenotype. Our data shows that developing juveniles are affected in their brain protein accumulation by elevated CO2, but the effect varies with the length of exposure as well as due to variation of parental phenotypes in the population.